Pembentukan Karakter Iman Anak Melalui Doa-Doa Harian Katolik di Stasi Santo Mikhael Ohoilimr through daily Catholic - Viktoria Stela Reyaan; Teresia Noiman Derung (Lembaga Pengembangan Kinerja Dosen, 2024)
Catholicism plays an important role in shaping children's faith character, which aims to regulate children's identity and morals in accordance with Christian teachings. This research takes the example of daily prayer practices at the St. Mikhael Ohoilim Station, where the researcher directly saw the lack of teaching and training in daily prayers at the station and its influence on the formation of children's faith character. The research method used is qualitative where data is collected through observation. This research was carried out while carrying out an internship or KKN for approximately six months starting from January to June at the Station in accordance with the rules made by a particular institution or campus. The research results show that daily prayers not only function as a means of communication with God, but also as an effective educational tool in forming religious values, discipline and a sense of responsibility in children.